STATE COMBAT MIGHT INCREASE ROLE OF IRREGULAR ARMED FORMATIONS IN MODERN ARMED CONFLICTS IN SYRIA AND UKRAINE - Целуйко, В. О. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2017)
The role of irregular armed formations in modern armed conflicts is examined through theexample of Syria and Ukraine. Their position in state military organization is determined. Thedependence of irregular formations involvement into combat activities scale upon regular statearmored forces genesis is substantiated. In case if the last ones are degraded, irregular formationsstart to take more important or even major part in combat standoff, as it happen in Syria.